2021
DOI: 10.3390/foods11010060
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Inclusion Complexes of Isothiocyanates with γ-Cyclodextrin for Improvement of Antibacterial Activities against Staphylococcus aureus

Abstract: The aim of this study was to develop inclusions formed by γ-cyclodextrin (γ-CD) and three isothiocyanates (ITCs), including benzyl isothiocyanate (BITC), phenethyl isothiocyanate (PEITC), and 3-methylthiopropyl isothiocyanate (MTPITC) to improve their controlled release for the inhibition of Staphylococcus aureus (S. aureus). These inclusion complexes were characterized using X-ray diffraction, Fourier-transform infrared, thermogravimetry, and scanning electron microscopy (SEM), providing appropriate evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…BITC−α−CD displayed a quite similar spectrum to that of α−CD, except for the existence of characteristic peaks at 2140–2040 cm −1 . In recent studies, BITC was reported to have absorption bands at 2140–2040 cm −1 attributed to the thiocyanate group and at 1600–1345 cm −1 ascribed to the benzene ring [ 10 , 38 ]. Moreover, the benzene ring of BITC was suggested to be entrapped in the cavity of γ−CD, whereas the thiocyanate moiety was exposed outside [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BITC−α−CD displayed a quite similar spectrum to that of α−CD, except for the existence of characteristic peaks at 2140–2040 cm −1 . In recent studies, BITC was reported to have absorption bands at 2140–2040 cm −1 attributed to the thiocyanate group and at 1600–1345 cm −1 ascribed to the benzene ring [ 10 , 38 ]. Moreover, the benzene ring of BITC was suggested to be entrapped in the cavity of γ−CD, whereas the thiocyanate moiety was exposed outside [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, BITC was reported to have absorption bands at 2140–2040 cm −1 attributed to the thiocyanate group and at 1600–1345 cm −1 ascribed to the benzene ring [ 10 , 38 ]. Moreover, the benzene ring of BITC was suggested to be entrapped in the cavity of γ−CD, whereas the thiocyanate moiety was exposed outside [ 38 ]. Another study entrapping BITC to β−CD reported a resemble inclusion complex pattern [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 1 a, the feature absorption bands of α-CD appear at 3400 cm −1 , 2926 cm −1 , 1156 cm −1 , 1078 cm −1 , and 1028 cm −1 , which belonged to the O-H symmetric stretching vibration, C-H stretching vibration, C-O-C glycosidic bridge stretching vibration, and C-O/C-C stretching vibrations, respectively [ 29 , 30 ]. The FTIR spectrum of pure MTPITC has been illustrated in our recent report, in which the prominent peak, displayed at around 2140–2040 cm −1 , corresponded to the thiocyanate group (N=C=S) [ 31 ]. In the current study, after being encompassed in the α-CD, the characteristic absorption peaks of MTPITC at 2140–2040 cm −1 were still observed, suggesting that MTPITC exists in the inclusion complex.…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus aureus is a Gram-positive bacterium that infects the human body and produces enterotoxins [ 1 , 2 ]. According to a report by the Centers for Disease Control and Prevention [ 3 , 4 ], approximately 241,000 foodborne diseases are caused by S. aureus each year in the United States, and it is the third most prevalent foodborne disease in the world [ 5 ], as it is often present in frozen and refrigerated food, such as meat, aquatic products, and ice cream [ 6 ].…”
Section: Introductionmentioning
confidence: 99%